Stainless Steels - Lacombe, P. Ed; Baroux, B. Ed; Beranger, G. Ed (Physique Les Ulis, 1993)
HISTORICAL PACKGROUND TO STAINLESS STEELS;STRUCTURE AND PROPERTIES;CORROSION RESISTANCE;THE MAJOR FAMILIES OF STAINLESS STEELS;SECONDARY PROCESSING;MANUFACTURE, APPLICATIONS AND STANDARIZATION